PENGARUH NILAI TUKAR RUPIAH DAN VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Made Linda Artini Putri; Ni Luh Kardani; Komang Asri Pratiwi (Nusantara Hasana Journal, 2023)
This study, entitled "The Effect of the Rupiah Exchange Rate and Stock Trading Volume on Stock Returns in Industrial Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period”, aims to determine and analyze the effect of the Rupiah Exchange Rate and Stock Trading Volume simultaneously and partially on company stock returns in the industrial sector listed on the Indonesia Stock Exchange for the 2017-2021 period. This research is a quantitative study. The population in this study is all industrial sector companies listed on the Indonesia Stock Exchange until 2021 or as many as 54 companies. The sampling technique used in this study was purposive sampling with certain criteria. The research sample in this study totaled 19 industrial sector companies listed on the Indonesia Stock Exchange. This study uses multiple linear regression analysis techniques. This study states that the Rupiah Exchange Rate has a positive and insignificant effect on stock returns in industrial sector companies listed on the Indonesia Stock Exchange for the 2017–2021 period, Stock trading volume has a positive and significant effect on share returns in industrial sector companies listed on the Indonesia Stock Exchange for the 2017–2021 period, The Rupiah Exchange Rate and Stock Trading Volume have a significant effect on industrial sector companies listed on the Indonesia Stock Exchange for the 2017–2021 period.